2016
DOI: 10.1016/j.vaccine.2016.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Influenza B vaccine lineage selection—An optimized trivalent vaccine

Abstract: HighlightsAlthough it is not known which one of two influenza B lineages will circulate in any one season, only a representative virus of one of the two lineages is part of the trivalent seasonal influenza vaccine.We describe three lineage selection strategies to choose which lineage to include in the seasonal vaccine, including the common strategy of using the last lineage that has been observed to dominate, and a new strategy which takes into account population immunity.We show why the “hedging strategy” lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…For the duration of vaccine-induced protection, a recent study by Kissling et al [57] suggested that protection against influenza B was longer than that against influenza A/H3N2, possibly due to a more rapid antigenic drift of A/H3N2 [61]. Related to this aspect, Höpping et al [62] recently presented an approach to optimize the effectiveness of TIV by choosing the included influenza B strain on the basis of the population's pre-existing immunity instead of taking the virus strain that circulated in the prior season. They argued that by taking into account the time since vaccination, antigenic drift, and serological parameters of each B virus strain, the level of residual protection against B/Yam and B/Vic could be estimated.…”
Section: Expert Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…For the duration of vaccine-induced protection, a recent study by Kissling et al [57] suggested that protection against influenza B was longer than that against influenza A/H3N2, possibly due to a more rapid antigenic drift of A/H3N2 [61]. Related to this aspect, Höpping et al [62] recently presented an approach to optimize the effectiveness of TIV by choosing the included influenza B strain on the basis of the population's pre-existing immunity instead of taking the virus strain that circulated in the prior season. They argued that by taking into account the time since vaccination, antigenic drift, and serological parameters of each B virus strain, the level of residual protection against B/Yam and B/Vic could be estimated.…”
Section: Expert Commentarymentioning
confidence: 99%
“…By selecting the influenza B virus strain with the lowest residual protection, high protection levels against both influenza B viruses would be present after vaccination, potentially giving a better protection in case of a vaccine mismatch. Although this strategy is expected to be still inferior to QIV, Höpping et al [62] suggested that it might at least partially capture the benefit of QIV, without any additional vaccine costs. So far, no study has ever compared the cost-effectiveness of QIV versus TIV using this 'Höpping' approach, which, however, might be of interest and complement existing studies.…”
Section: Expert Commentarymentioning
confidence: 99%
“…Some studies support the inclusion of both lineages of influenza B virus in the vaccine to reduce illness ( 38 ), although others suggest a more cautious approach, arguing that addition of a second influenza B virus lineage leads to a modest reduction in influenza-associated outcomes ( 39 ). Recently, a hedging strategy for selection of the influenza B virus lineage included in the standard trivalent vaccine has been suggested as the most effective in terms of long-term protection rates ( 40 ). …”
Section: Discussionmentioning
confidence: 99%
“…Despite the limited number of existing IBV lineages, vaccine strain selection is still difficult because the dominant lineage changes over time and the switching time of the dominant lineage is difficult to predict. Although the quadrivalent vaccine includes both IBV lineages, Höpping et al 2016 pointed out the necessity of vaccine strain selection because the use of trivalent vaccines is still common worldwide and the cost-effectiveness of quadrivalent vaccines is under debate [4]. …”
Section: Introductionmentioning
confidence: 99%
“…The time series of confirmed cases between two lineages are negatively correlated (Fig 1), implying epidemiological interference between the two lineages. Moreover, vaccine efficacy studies also imply the existence of immune cross-reaction between lineages [4]. The epidemic dynamics of a lineage are affected by that of the other lineage assuming the existence of immune cross-reaction.…”
Section: Introductionmentioning
confidence: 99%